Loss of the wild-type allele contributes to myeloid expansion and disease aggressiveness in FLT3/ITD knockin mice - Li, Li (American Society of Hematology, 2011)
Clinical evidence has shown that FLT3 internal tandem duplication (ITD) mutation confers poor prognosis in acute myeloid leukemia. Loss of the FLT3 wild-type (WT) allele is associated with even worse prognosis. We have previously reported that heterozygous FLT3(wt/ITD) “knockin” mice develop a slowly fatal myeloproliferative neoplasm (MPN). To study the roles of the WT FLT3 and ITD alleles in the development of MPNs, we generated FLT3/ITD homozygous (FLT3(ITD/ITD)) and hemizygous (FLT3(−/ITD)) mice. FLT3(−/ITD) mice, with the loss of WT allele, display a more severe MPN, as evidenced by even larger spleen, higher white blood cell counts, and shorter survival, compared with FLT3(wt/ITD) mice. Reintroduction of the WT FLT3 allele into FLT3(−/ITD) BM slowed the progression of MPN in recipient mice. FLT3(ITD/ITD) mice had an even severe MPN compared with the FLT3(−/ITD) and FLT3(wt/ITD) mice. Spontaneous leukemia developed in a small fraction of the FLT3(ITD/ITD) mice but was never observed in the FLT3(−/ITD) and FLT3(wt/ITD) mice. Our results suggest that loss of the WT allele contributes to the development of a more severe phenotype. Thus, the WT FLT3 allele seemingly functions as a tumor suppressor, attenuating the function of the FLT3/ITD allele in leukemia harboring FLT3/ITD mutations.